Programming Arduino: Getting Started with Sketches, Third Edition - Monk, Simon (McGraw-Hill/Osborne, 2023)
Programming Arduino: Getting Started with Sketches, Third Edition features dozens of easy-to-follow examples and high-quality illustrations. All of the sample sketches featured in the book can be used as is or modified to suit your needs. You will also get all new coverage of using Arduino as a framework for programming other popular boards. --